Beauty is wealth: CEO attractiveness and firm value. Issue 4 (1st June 2020) - Halford, Joseph T.; Hsu, Hung‐Chia S.
Abstract: This paper examines whether and how CEO attractiveness relates to firm value. We construct a Facial Attractiveness Index of 667 CEOs based on their facial geometry. More attractive CEOs are associated with better stock returns surrounding their job announcements and around earnings‐announcement news with CEOs' images. Further, more attractive CEOs are related to higher acquirer returns following acquisition announcements and higher Tobin's Q . Finally, consistent with the existing literature documenting the beauty premium in pay, more attractive CEOs receive higher compensation.